2022
DOI: 10.3389/fmicb.2022.929725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tillage and biochar on soil physiochemical and microbial properties and its linkage with crop yield

Abstract: Vertisols are clayey soils with a high potential for improving production. Therefore, understanding the impact of tillage and fertilization on soil physicochemical properties and microbial community is essential for improving the vertisols with a high montmorillonite and smectite clay content. A 3-year field experiment was conducted to compare the effects of different tillage and fertilization practices at three depths of the vertisol under the wheat–maize cropping system in the North China Plain. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Gaiella is a genus of Gaiellales, several researchers revealed that they were widely distributed in the rhizosphere of different plant species and could reduce the content of nitrate, helping plants better absorb nutrients from the soil [52][53][54]. Another study also found that there was a significant positive correlation between crop yield and the abundance of Gaiellalea [55]. The RDA and co-occurrence network analyses both indicated that the relative abundance of Gaiellales was positively correlated with soil-available phosphorus, urease, and amylase.…”
Section: Abundance Of Soil Nutrients Releasing Relevant Microbes Are ...mentioning
confidence: 99%
“…Gaiella is a genus of Gaiellales, several researchers revealed that they were widely distributed in the rhizosphere of different plant species and could reduce the content of nitrate, helping plants better absorb nutrients from the soil [52][53][54]. Another study also found that there was a significant positive correlation between crop yield and the abundance of Gaiellalea [55]. The RDA and co-occurrence network analyses both indicated that the relative abundance of Gaiellales was positively correlated with soil-available phosphorus, urease, and amylase.…”
Section: Abundance Of Soil Nutrients Releasing Relevant Microbes Are ...mentioning
confidence: 99%
“…Organic nutrient amendments and tillage systems have been frequently suggested as critical aspects of food security under the changing climate, however, responsible agronomic-based solutions should follow a food system and circular economy approaches. The adaptation of minimum tillage in combination with organic amendments, including biochar, may sustain the soil health indicators i.e., increase nitrogen status, soil organic carbon, and phosphorus [122] to support crop growth and environmental sustainability by reducing soil erosion and carbon emissions [123]. It is also worth mentioning that a combined effect of biochar application and deep tillage has significantly decreased bulk density, increased the air capacity of the soil, and enhanced the soil organic carbon content and available phosphorus, which subsequently enhances the grain yield of crops [124,125].…”
Section: Interactive Effects Of Tillage System and Biochar Applicatio...mentioning
confidence: 99%